Aplikasi Teknologi Ramah Lingkungan Pada Industri Penyamakan Kulit Di Settebello, Italia (Sebuah Hasil Analisis Studi Magang Industri Mahasiswa) - A. Nurazizah Taufiq; Andi Muh. Nurcholish Pasha; Fadli Hasdin; Muhammad Irfan Said; Muhammad Ihsan Andi Dagong; Mehmet Mete Mutlu; Constantina Kollia; Maurizia Seggiani; Gabriella Romaito Br Manalu (Universitas Mataram, 2025)
The tanning industry is known as one of the sectors that produces hazardous waste due to the use of chemicals such as chromium and sodium sulfide, so the application of safer and more sustainable technology is needed. This study aims to evaluate the implementation of environmentally friendly technology in the Settebello tanning industry in Italy through direct observation focusing on the principles of green chemistry and Best Available Techniques. The results show that Settebello has implemented digital process control, a recirculation-based water efficiency system, and the use of enzymatic tanning at the dehairing, bating, and degreasing stages to replace harsh chemicals that have the potential to pollute the environment. The application of this technology has been proven to be able to reduce the pollution burden, improve the consistency of skin quality, and reduce health risks for workers through reducing exposure to harmful substances. In addition, chromium recovery and integrated waste treatment contribute to improving resource efficiency and strengthening the sustainability of the production process. These findings confirm that cleaner tanning technology can be effectively applied in industrial operations and has great potential to be adapted by the tanning sector in Indonesia as an effort to support the improvement of environmental performance, process efficiency, and national industrial competitiveness. The application of these innovations also opens up opportunities for the development of advanced research that focuses on process optimization, emission reduction, and expansion of sustainability standards for the tanning industry in the future.